Análisis de Competencias Laborales a Nivel Gerencial en el Sector Automotríz con Egresados de una Universidad Pública del Estado de Guanajuato. - Molina García, María Guadalupe (Revista Daena: International Journal of Good Conscience, 2012)
In this part of the research process shows progress of the author's doctoral thesis which seeks to offer from the union between practice and academy to the diagnosis of labor markets, monitoring and trend analysis and it also addresses the issue of understanding the relationships that this problem occurs in a particular moment in time when comparing the self-evaluations among recent graduates with self-assessments of people who are at a high level position in the automotive sector Guanajuato and therefore, to establish the gap with those administrative economic area students, and identify which competences should be developed to reach a position with a high level of responsibility to a greater degree of certainly to which an instrument used widely tested, the results and findings until now.